Documentation of Indigenous Knowledge on Mushroom Cultivation - Sagar, M P; Ahlawat , O.P.; Vijay, B. (Indian Journal of Extension Education, 2014)
Mushroom cultivation in India is being practised for the last four decades. During this period, mushroom growers have  amended several scientifically proven mushroom cultivation practices suiting to their own needs. The collection and  documentation of such locally adopted practices is very important from view point of their validation and further  refinement. Thus, the present study was conducted by involving 400 established mushroom growers, and  research/extension personnel using mailed questionnaire and structured interview schedule. A total of 10 ITKs were  collected on different aspects of button, oyster and paddy straw mushrooms. Majority of the collected ITKs were on  button mushroom, while only a few on oyster and paddy straw mushrooms. The ITKs viz., pasteurization of button  mushroom compost without injecting steam, use of burnt rice husk as casing material for button mushroom, mushroom  growing in mud houses and thatched / sarkanda sheds, cooling system of thatched shed/pakka house, spray of urea and  English wishkey (alcohol) on mushroom beds, bunker system and under stacking aeration system for button mushroom  compost preparation, flat floor method of oyster mushroom cultivation and traditional outdoor and indoor methods of  paddy straw mushroom cultivation were collected. These ITKs need to be validated and refined through experiments,  experts opinion and scientific literature.
Keywords: Indigenous technical knowledge; mushroom cultivation; button mushroom; paddy straw mushroom; oyster mushroom